Falsafah al-Lugah wa al-Fikr: Atsaruhuma fi at-Ta'lim wa Ta'allum al-Lugah al-Arabiyah - Kafi, Fina Aunul; Halimi, Halimi (Al-Fusha : Arabic Language Education Journal, 2024)
The philosophy of language and mind plays an important role in language learning, especially in the context of Arabic language learning. However, more in-depth research is needed to understand the implications of these philosophical concepts in Arabic language learning. This study aims to investigate the implications of the philosophy of language and mind in the context of Arabic language learning. The research method used is library research, which involves a review of literature related to philosophy of language, philosophy of mind, and Arabic language learning. Analysis of the literature shows that philosophy-based approaches can be an important basis in learning development, including curriculum development, learning methods, and teacher and student skills. The implications of the findings highlight the importance of adopting a philosophy-based approach to Arabic language learning by designing curriculum and teaching methods that take into account the close relationship between language and mind.